Investment Law Reform : A Handbook for Development Practitioners - World Bank Group (World Bank, Washington, DC, 2016)
The chief purpose of this handbook is to provide government lawyers with a framework to evaluate the quality of a country's investment legislation (if it exists) and how the legislation relates to its investment policy and investment incentives. More specifically, it deals with creating new and reforming existing investment legislation in developing and transition economies in furtherance of the World Bank Group's (WBG's) mandate to promote private investment - domestic and foreign - in those economies. Handbook appendices contain drafting guidelines and checklist of issues that foreign direct investment (FDI) laws should include and that countries can use when drafting investment legislation. The report is structured as follows: chapter one defines key terms about investment law reform in an effort to clarify terminology and concepts and show how they are related. Chapter two examines how widespread investment codes are and explains their utility and limitations. Chapter three provides recommendations on the structure of investment legislation and the key provisions to be included such as definitions, investors' guarantees, incentives, framework for investment promotion, and transitional provisions. Chapter four discusses the fundamental issue of investor entry, in particular the conditions under which foreign investors can invest including sectoral restrictions, limitations on foreign ownership, authorization and screening, minimum investment, and performance requirements. Chapter five discusses key investor guarantees including fair and equitable treatment, national treatment, most-favored-nation (MFN) treatment, protection against expropriation, guaranteed convertibility and repatriation of profits, and settlement of disputes. Chapter six looks at the issue of investment incentives, (fiscal incentives in particular) and their effectiveness. Chapter seven summarizes key aspects of investment promotion to guide legal drafters, should policymakers want the investment code to set out the basic framework of investment promotion. Chapter eight presents the various phases of investment law reform projects, from the government's request for assistance with legislation to the delivery of a project plan. Chapter nine identifies some of the challenges in preparing an investment code and the support that governments may need until the law is promulgated. Chapter ten discusses the monitoring and evaluation (M and E) of investment law reforms, including the key indicators involved in a desk review and medium- and large-scale projects.